PENGARUH FIRM SIZE, LABA RUGI, OPINI AUDITOR TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Siti Tiffanny Guci; Rosiana Clarita; Mellisa ,; Jimmy Ronaldo; Wilbert Howard; Ricardo ,; Isna Asdiani Nasution (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2019)
The financial report has an important role in the survival of a company, the report is based on Bapepam Regulation No. X.K. 2, appendix to the Decree of the Chairman of Bapepam-No. KEP-36/PMK/2003 concerning Report Submission Obligations Periodic Financial, "Bapepam requires that every public company registered in the capital market shall submit an annual financial report accompanied by an independent audit report to Bapepam at the latest by the end of the third month (90 days). The annual financial report date. Therefore, researchers take some of the factors that affect the audit delay, namely the size of the company, profit or loss, the auditor's opinion, and test their influence on the audit delay in the mining sector companies listed on the IDX. The research method used is quantitative research with data collection using secondary data derived from financial statements on IDX. The population in this study amounted to 45 companies. Samples used as much as 36 companies. The results of this research show that a partial firm size and opinion auditors have no effect on the audit delay, but on the profit or loss affects the audit delay. As for the simultaneous firm size, profit or loss, the auditor's opinion affects the audit delay.